2011
DOI: 10.1038/ki.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant glycosylation of IgA1 is inherited in both pediatric IgA nephropathy and Henoch–Schönlein purpura nephritis

Abstract: Serum galactose-deficient IgA1 (Gd-IgA1) is an inherited risk factor for adult IgA nephropathy (IgAN). The goal of this study is to determine the heritability of serum Gd-IgA1 levels in children with IgAN and Henoch-Schönlein nephritis (HSPN). For this purpose, we obtained serum from 34 Caucasian families (20 pediatric cases of HSPN, 14 pediatric cases of IgAN, and 54 of their first-degree relatives), as well as from 51 age- and ethnicity-matched pediatric controls and 141 healthy adult controls. Serum Gd-IgA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
130
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(139 citation statements)
references
References 39 publications
7
130
0
2
Order By: Relevance
“…This finding is consistent with a multi-hit hypothesis for the disease mechanism of IgAN, wherein an increased serum level of autoantigen alone is not sufficient to induce renal injury [25][26][27] ; it must combine with autoantibodies either in the circulation to form immune complexes that deposit in the glomerular mesangium or in situ with Gd-IgA1 already in the mesangium. Based on the physical and biologic characteristics of the immune complexes, such as composition and size, 17,28 mesangial cells may be activated to proliferate and overproduce components of mesangial matrix, chemokines, and cytokines.…”
Section: Discussionsupporting
confidence: 76%
“…This finding is consistent with a multi-hit hypothesis for the disease mechanism of IgAN, wherein an increased serum level of autoantigen alone is not sufficient to induce renal injury [25][26][27] ; it must combine with autoantibodies either in the circulation to form immune complexes that deposit in the glomerular mesangium or in situ with Gd-IgA1 already in the mesangium. Based on the physical and biologic characteristics of the immune complexes, such as composition and size, 17,28 mesangial cells may be activated to proliferate and overproduce components of mesangial matrix, chemokines, and cytokines.…”
Section: Discussionsupporting
confidence: 76%
“…Variations in the identified risk loci are distributed at different frequencies in different populations, thereby explaining the wide range in the incidence of IgAN among different ethnic groups [47]. No genome-wide association study has yet been performed in patients with HSPN, but it has been shown that Gd-IgA1 serum levels are inherited in both IgAN and HSPN, suggesting that the genetic predisposition for developing HSPN is the same as that for developing IgAN [48]. In summary, acute and chronic glomerular damage in HSPN is thought to be the result of mesangial Gd-IgA1-containing immune complex deposition, potentially mediated by mesangial receptors, and the ensuing complement-mediated stimulation of the mesangial cells, leading to their proliferation and cytokine secretion (Fig.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…Heritability of gd-IgA1 has previously been demonstrated in studies based on families ascertained through the presence of IgA nephropathy or HenochSchonlein Purpura, although estimates were sometimes dependent on the gdIgA1 levels of the index case. [25][26][27] An increased level of gd-IgA1 is associated with IgAN and is considered to be the 'first hit' in the proposed disease pathogenesis model. 8,20 Notably, asymptomatic first-degree relatives of IgAN patients have high gd-IgA1 levels, suggesting that additional factors ('hits') are required for IgAN to develop.…”
mentioning
confidence: 99%
“…23,24,25 Studies of familial IgAN have provided heritability estimates for gd-IgA1 between 54% and 76%. [25][26][27] One difficulty of these studies is that at-risk relatives tend to show increased gd-IgA1 levels, biasing the heritability estimates which have been suggested to strongly depend on the gd-IgA1 levels of the index IgAN case. 26 In order to understand the genetic contribution to gd-IgA1 levels in IgAN patients, it is first necessary to understand the genetic contribution to gd-IgA1 levels in healthy individuals.…”
mentioning
confidence: 99%